Estimation of effective dose from CT scanning using dose length product in a Nepalese hospital - Shah, Pooja (Radiography Open, 2020)
Keywords: Effective dose, Dose Length Product, Computed Tomography Dose Index volume, Dose Reference Level Abstract Aim: The aim of this study was to estimate the effective doses from CT scans using Dose Length Product (DLP) in a Nepalese hospital. Materials and methods: This prospective study was conducted in 150 patients above 18 years of age who were referred for CT scan of head, chest and abdomen. The CT scan was performed on a 128 slice multi detector scanner. All the subjects who met the inclusion criteria were included in the study. Following the non-contrast imaging phases of the head, chest and abdomen CTDIvol, DLP, kVp and pitch were recorded for each patient from the console display of the scanner. The effective dose was calculated for each examination using DLP which were graphically analyzed and correlated with the age of the patient. Results: The study showed the mean CTDIvol for head, chest and abdomen to be 53.95±4.83 mGy, 5.28±1.17 mGy and 11.15±2.71 mGy respectively along with mean DLP to be 923.52±71.11 mGycm, 229.32±48.70 mGycm and 517.02±148.32 mGycm respectively. Using these values, the mean effective doses were calculated and found to be 1.93±0.14 mSv, 3.20±0.68 mSv and 7.75±2.19 mSv respectively. Conclusion: The calculated effective dose values were lower than in other studies for CT examinations of chest and abdomen while higher or similar for CT examination of head. The results of this survey could motivate other researchers to investigate the radiation doses in other hospitals and help establish national diagnostic reference levels.